EXAMINING THE RELATIONSHIP BETWEEN THE E-SERVICE QUALITY OF INDONESIAN FASHION RETAILERS’ E-COMMERCE WEBSITES, CUSTOMER SATISFACTION, AND PURCHASE INTENTION - Wiliam Santoso; Hadi Kusuma Sunyoto; Hosea Kristo Listyatmadja; Stevano James Hermanto; Berlin Fitoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research identifies several factors influencing Indonesian fashion retailers’ intention to buy through e-commerce websites or applications, specifically, e-service quality and customer satisfaction. This study uses a quantitative descriptive method by disseminating questionnaires to 300 respondents across Indonesia with the specification of having mobile phones, having connected to the internet, and having purchased products online at least once from Indonesian fashion retailers such as H&M, Uniqlo, Zara, Pull&Bear, etc. This study confirmed that out of the five dimensions of e-service quality, only reliability, personalization, and trust positively influence overall e-service quality. Additionally, overall e-service quality positively influenced customer satisfaction and purchase intention. Moreover, customer satisfaction positively and significantly influences purchase intention because it has the highest R². Lastly, customer satisfaction was found to mediate the relationship between overall e-service quality and purchase intention through the Sobel test. Future scholars are suggested to explore alternative variables and delve into other sectors within the digital realm beyond the fashion industry to strengthen the validity of this study. They also may consider sampling from broader scopes, such as the ASEAN region or even at the Asian level, to improve the comprehensiveness of their research.